Multidisciplinary Treatment of the Metabolic Syndrome Lowers Blood Pressure Variability Independent of Blood Pressure Control. Issue 1 (26th September 2015) - Marcus, Yonit; Segev, Elad; Shefer, Gabi; Sack, Jessica; Tal, Brurya; Yaron, Marianna; Carmeli, Eli; Shefer, Lili; Margaliot, Miri; Limor, Rona; Gilad, Suzan; Sofer, Yael; et al.
Abstract : Blood pressure (BP) variability (BPV) contributes to target organ damage independent of BP. The authors examined the effect of a 1‐year multidisciplinary intervention on BPV in patients with the metabolic syndrome (MetS) as defined by criteria from the Third Report of the Adult Treatment Panel. Forty‐four nondiabetic patients underwent clinical and biochemical profiling, 24‐hour ambulatory BP monitoring (ABPM), body composition, carotid intima‐media thickness, and carotid‐femoral pulse wave velocity (PWV). The intervention targeted all MetS components. BPV was assessed by the standard deviation of daytime systolic BP derived from ABPM. Patients with low and high BPV (lower or higher than the median daytime standard deviation of 11.6 mm Hg) did not differ in regards to systolic and diastolic BP, age, fasting glucose, glycated hemoglobin, and body mass index, but the high‐variability group had higher values of low‐density lipoprotein and leg fat. The 1‐year intervention resulted in weight reduction but not BP‐lowering. BPV declined in the high‐variability group in association with lowering of PWV, C‐reactive protein, glycated hemoglobin, alanine aminotransferase, asymmetric dimethylarginine, and increased high‐density lipoprotein cholesterol. A multidisciplinary intervention independent of BP‐lowering normalized BPV, lowered PWV, and enhanced metabolic control.